2008
DOI: 10.1186/1471-2288-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Intervention, recruitment and evaluation challenges in the Bangladeshi community: Experience from a peer lead educational course

Abstract: BackgroundThe incidence of Type 2 diabetes is increasing worldwide and diabetes is four times more common among ethnic minority groups than among the general Caucasian population. This study reflects on the specific issues of engaging people and evaluating interventions through written questionnaires within older ethnic minority groups.MethodsThe original protocol set out to evaluate an adapted version of the X-PERT® patient program using questionnaires and interviews.ResultsQuestionnaires, even verbally comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Among education studies conducted in Europe targeting knowledge of and practices related to diabetes, education intervention was not consistently associated with the improvement of the outcomes. Specifically, while half of the studies reported an improvement in knowledge of and attitudes and behaviours related to diabetes, the other half either found no such improvement 14 or the difference in mean change scores between the intervention and control groups did not differ. 15 Improvement in knowledge was observed in men and women and across literacy levels in one study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Among education studies conducted in Europe targeting knowledge of and practices related to diabetes, education intervention was not consistently associated with the improvement of the outcomes. Specifically, while half of the studies reported an improvement in knowledge of and attitudes and behaviours related to diabetes, the other half either found no such improvement 14 or the difference in mean change scores between the intervention and control groups did not differ. 15 Improvement in knowledge was observed in men and women and across literacy levels in one study.…”
Section: Resultsmentioning
confidence: 94%
“…One study 15 included a dietician and podiatrist to provide education using didactic and interactive sessions with visual aids. The other 14 used peer educators trained by a general practitioner with a special interest in diabetes to provide educational sessions giving advice on exercise, diet, attending appointments, cultural behaviours and the development of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…A second education-based intervention, X-PERT, has also been tested in an RCT, and a range of benefits were reported on physiological and behavioral outcomes, including improved glycemic control, BMI, diet, and self-management skills at 14 months [ 77 ]. A noncontrolled trial of an adaptation of the program designed for Bangladeshi adults with type 2 diabetes, which did not involve GP referral and therefore is not included in the tables, has also been completed but was underpowered due to low attendance rates [ 108 , 109 ]. A program designed specifically for Muslim diabetics was also assessed by retrospective analysis and reported beneficial effects [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the effectiveness of structured diabetes education has been demonstrated , there is evidence that many education programmes are considerably less successful in people from ethnic minority groups . This is often attributed to the failure of generic diabetes education to account for cultural beliefs and language requirements . Culturally appropriate diabetes education interventions targeted at specific ethnic groups are highly varied in nature and rarely assessed in randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%